Creating Structured PDF Files Using XML Templates - Hardy, Matthew; Brailsford, David F.; Thomas, Peter (ACM Press, 2004)
This paper describes a tool for recombining the logical structure from an XML document with the typeset appearance of the corresponding PDF document. The tool uses the XML representation as a template for the insertion of the logical structure into the existing PDF document, thereby creating a Structured/Tagged PDF. The addition of logical structure adds value to the PDF in three ways: the accessibility is improved (PDF screen readers for visually impaired users perform better), media options are enhanced (the ability to reflow PDF documents, using structure as a guide, makes PDF viable for use on hand-held devices) and the re-usability of the PDF documents benefits greatly from the presence of an XML-like structure tree to guide the process of text retrieval in reading order (e.g. when interfacing to XML applications and databases).